Educational Change Amongst English Language College Teachers in China Transitioning from Teaching for General to Academic Purposes - Li, Yulong (Springer Nature, 2020)
This open access book provides anthropological insights into the arduous yet rewarding journeys involved in selected TESOL teachers' pedagogical transition to teaching English for Academic Purposes (EAP) at universities in Shanghai, the largest metropolitan area in China. Applying a unique combination of ethnography and phenomenology, the book offers innovative new perspectives on teacher education research. Drawing on the latest language education theory, it outlines a practitioner-friendly approach to EAP literacy. Teacher readers will especially benefit from the case studies presented here, which provide role models for teacher change in educational reform, as well as advice on their academic careers. In addition to addressing a timely and important research gap on EAP teachers in non-Western countries, the book is the ideal choice for readers interested in an update on English education in China.